Etiologies of severe acute respiratory infection (SARI) and misdiagnosis of influenza in Indonesia, 2013‐2016. Issue 1 (14th July 2020) - Aman, Abu Tholib; Wibawa, Tri; Kosasih, Herman; Asdie, Rizka Humardewayanti; Safitri, Ida; Intansari, Umi Solekhah; Mawarti, Yuli; Sudarmono, Pratiwi; Arif, Mansyur; Puspitasari, Dwiyanti; Alisjahbana, Bachti; Parwati, Ketut Tuti Merati; et al.
Abstract: Background: Severe acute respiratory infection (SARI) accounts for a large burden of illness in Indonesia. However, epidemiology of SARI in tertiary hospitals in Indonesia is unknown. This study sought to assess the burden, clinical characteristics, and etiologies of SARI and concordance of clinical diagnosis with confirmed etiology. Methods: Data and samples were collected from subjects presenting with SARI as part of the acute febrile Illness requiring hospitalization study (AFIRE). In tertiary hospitals, clinical diagnosis was ascertained from chart review. Samples were analyzed to determine the "true" etiology of SARI at hospitals and Indonesia Research Partnership on Infectious Diseases (INA‐RESPOND) laboratory. Distribution and characteristics of SARI by true etiology and accuracy of clinical diagnosis were assessed. Results: Four hundred and twenty of 1464 AFIRE subjects presented with SARI; etiology was identified in 242 (57.6%), including 121 (28.8%) viruses and bacteria associated with systemic infections, 70 (16.7%) respiratory bacteria and viruses other than influenza virus, and 51 (12.1%) influenza virus cases. None of these influenza patients were accurately diagnosed as having influenza during hospitalization. Conclusions: Influenza was misdiagnosed among all patients presenting with SARI to Indonesian tertiary hospitals in the AFIRE study. Diagnostic approaches and empiric management should be guided by known epidemiology. Public health strategies to address the high burden of influenza should include broad implementation of SARI screening, vaccination programs, clinician education and awareness campaigns, improved diagnostic capacity, and support for effective point‐of‐care tests.